Sistem Informasi Geografis Untuk Pelaporan Dan Pelacakan Kejahatan Berbasis Android Pada Polres Gorontalo Kota - Lasena, Marlin; Ahmad, Sulistiawati Rahayu Ningsi (Jurnal Teknologi Informasi Indonesia (JTII), 2020)
Geographic Information Systems (GIS) is a computer-based information system for storing, managing and analyzing, and calling geographic differential data that has grown rapidly in the last five years. This rapid technological advance has led more and more people to benefit, one of which is to provide information on crime reporting and tracking in the city's Gorontalo police. This research is focused on the city's Gorontalo police related to reporting and tracking information especially related to crime location information. From the results of the study found that there is still very little use of technology to present information to the police in Gorontalo city, this is certainly a condition that irony in the midst of the rapid state of technology development today. Research System is implemented and can make it easier to provide information navigation point location reporting and tracking crimes that occur in Gorontalo police area of the city and have been through system testing (Blackbox and Whitebox).